Pengaruh Rasio Keuangan Terhadap Aktivitas Tax Avoidance - Lim, Setiadi Alim (Universitas Katolik Darma Cendika, 2025)
Taxes are deducted from net income and are classified as costs for the company. There is a tendency for companies to reduce the amount of tax paid to maximize the amount of profit. Efforts to reduce the amount of tax paid, some violate tax provisions and regulations (tax evasion), and some do not violate tax provisions and regulations (tax avoidance). Tax avoidance is one of the important issues that is widely studied. This study examines tax avoidance and is intended to obtain evidence of whether there is an effect of financial ratios on tax avoidance. There are five financial ratios used in this study, namely return on assets, leverage, company size, property, plant and equipment, and cash flow from operations which are used as independent variables. While the dependent variable is tax avoidance. The research conducted is classified as quantitative research and is intended to test the developed hypothesis. The population of the study is all companies on the Indonesia Stock Exchange (IDX) engaged in the pharmaceutical business. Sampling using the non-probability purposive sampling method and 10 sample companies were obtained. The data used are company financial report data from 2013-2023. Data analysis using multiple linear regression. The results of the study indicate that simultaneously (F test) all independent variables have an effect on the dependent variable. However, when a partial analysis (t test) is carried out, of the five independent variables used, only one independent variable has an effect on the dependent variable. The financial ratios that have an effect on tax avoidance are property, plant and equipment, while the other four financial ratios, namely return on assets, leverage, company size, and cash flow from operations, do not have an effect on tax avoidance. The results of this study differ from several previous studies. Several previous studies showed that the five independent variables partially had an effect on the dependent variable. The difference in the results of this study may be because the companies studied were not heterogeneous in their business fields, only limited to companies with pharmaceutical business fields.